Analisis Upaya Wajib Pajak Melakukan Tax Avoidance Melalui Hibah - B.M, Afrizal Izzaki; Wijaya, Suparna (Jurnal Ilmiah Akuntansi Kesatuan, 2017)
A grant is a gift from a taxpayer to another taxpayer. For the recipient of the grant can be an income that is not a tax object or a tax object. This paper aims to provide an overview of the efforts made by taxpayers in tax avoidance through grants. The method used is qualitative with descriptive approach. The results show that taxpayers use grants as an attempt to avoid taxes through grants to educational institutions, parents to children, and the recognition of property that comes from grants